Marketingowe aspekty usług turystycznych - Koreleski, Dariusz (Marketing Aspects of Tourist Services, 2005)
The paper deals with the essence of the issue of services and the concept of marketing approach to tourist services. The author tries to present some intrinsic elements and determinants of marketing of services which may lead a service-seller to the market success. Special attention has been paid to the role of the force of habit, which very often affects the consumer surplus while rendering the service. The objective approach to the quality of a service, as well as the subjective one, has been pointed out and the role of personal impression has been underlined. The typology of tourists, reflecting their preferences has also been shown, so as to help a service-seller to adjust to people's habits and expectations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 468-472